PENGGUNAAN GAYA BAHASA DALAM KUMPULAN PUISI PADA AKUN INSTAGRAM PANJIRAMDANA - Giftia, Shofa Hilwa; Riyadi, Sugeng (Universitas Hamzanwadi, 2022)
To find out the aspects contained in Panjiramdana’s collection of poems on Instagram with a stylistic stude in the form of language style. The research method used is descriptive with an approach or search to explore and understand the topic being researched, using observation, interviews, analysis, and other data collection methpods. The results of the research on the use of language styles found in a collection of poems on Instagram @panjiramdanaofficial are as many as 7 language styles. The use of figurative language is found in 20 poems. Here are the details of the data: 5 Hyperbole, 2 Irony, 5 Sarcasm, 6 Simile, 3 Metaphor, 8 Personification dan 6 Climax.Keywords: language style, Panji Ramdana, Instagram